1994
DOI: 10.1364/josaa.11.001958
|View full text |Cite
|
Sign up to set email alerts
|

Foveal flicker sensitivity in healthy aging eyes II Cross-sectional aging trends from 18 through 77 years of age

Abstract: Foveal flicker contrast sensitivity was measured for healthy adults at temporal frequencies from 2.5 to 50 Hz. The first experiment compared two-interval forced-choice (2IFC) and yes-no detection (Y-N) testing procedures for younger (19-33-year-old) and older (67-73-year-old) observers. The 2IFC technique resulted in higher absolute estimates of sensitivity. However, within a method, relative differences were similar. Therefore the two methods gave similar estimates of temporal contrast-sensitivity change with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 19 publications
10
62
1
Order By: Relevance
“…Psychophysical methods have been used to derive an IRF from two-pulse thresholds and from tCSFs for stimuli modulated in luminance. The two approaches agree reasonably well 1,2 and are also qualitatively consistent with earlier studies of critical flicker frequency (CFF), considering that the latter seldom took account of retinal illuminance changes in the older retina due to reductions in pupil area and lenticular transmission. 3,4 In our previous study, 2 we measured two-pulse thresholds 5 for an achromatic test patch with a spatial Gaussian shape superimposed on a 10 cd/ m 2 background having the same chromaticity as the pulse.…”
Section: Introductionsupporting
confidence: 86%
“…Psychophysical methods have been used to derive an IRF from two-pulse thresholds and from tCSFs for stimuli modulated in luminance. The two approaches agree reasonably well 1,2 and are also qualitatively consistent with earlier studies of critical flicker frequency (CFF), considering that the latter seldom took account of retinal illuminance changes in the older retina due to reductions in pupil area and lenticular transmission. 3,4 In our previous study, 2 we measured two-pulse thresholds 5 for an achromatic test patch with a spatial Gaussian shape superimposed on a 10 cd/ m 2 background having the same chromaticity as the pulse.…”
Section: Introductionsupporting
confidence: 86%
“…More interesting, given the current context, was the finding that tIRFs of older observers consistently demonstrated reduced amplitude for the initial excitatory phase with no systematic age differences in the latency of the peak response (or zero crossing between response phases). Hence, Shinomori and Werner (2003) were able to independently confirm the previous conclusion of Kim and Mayer (1994) using an entirely different approach. It would appear, therefore, that age-related changes in flicker sensitivity are indicative of reduced contrast sensitivity within temporally tuned visual mechanisms instead of a more generalized slowing in visual processing.…”
Section: Flicker Sensitivitysupporting
confidence: 53%
“…Unlike Tyler's (1989) study, they failed to observe a leftward shift in the overall shape of the tCSF in their older observers and concluded that aging was characterized by a reduction in sensitivity of temporally tuned visual mechanisms rather than a generalized ''slowing'' in the rate of visual processing. Additional data analyses conducted by Kim and Mayer (1994) provided support for this interpretation of their data. According to linear systems theory, the impulse response function (IRF) quantitatively describes the response of the visual system to temporally modulated stimulus input.…”
Section: Flicker Sensitivitymentioning
confidence: 58%
“…17 In the healthy population, the TCS as a function of age shows three phases. 19,20 The first phase, where the TCS increases, is up to an age of approximately 16 years. From 16 to 60 years, the TCS is relatively constant.…”
Section: Introductionmentioning
confidence: 99%